A customização no atendimento como fator de fidelização do cliente às lojas de decoração de alto estilo - Silva, Paulo Cezar Ribeiro da (2001)
This study investigates how far customization in attendance act as clients faithfulness factor in top style interior design stores in Great Vitoria. After relative economic stability was reached with ¿Plano Real¿, customers could visualize better their money and consequently gave it more value. When clients acquire a product and demand high quality attendance they consider much beyond price. They want something new. Something that surprise. They are not satisfied only with what is best. They want the utmost. Do what is best is no longer a competitive advantage. It is now just a duty. Emphasizes application of custom-made attendance according to client specific needs as a competitive advantage-key to be pursued by companies. Analyses using extensive literature review including the world wide web source, the problem main theoretical fundaments. An intentional sample was used and interviews with closed questions were carried out with 230 clients and 18 store managers, to collect directly involved agents impressions. Conclusions show a mature customer, highly educated with good income and that demand exclusive treatment. In majority the study shows that customized attendance creates client faithfulness to top style interior design stores provided that price and product quality are adequate. Knowledge acquired with this study on attendance customization can give important contributions to top style interior design segment giving stores stimulus in the adoption of this distinctive competence facing growing global competitive market.